Analisis Strategi Promosi Digital Dalam Meningkatkan Volume Penjualan Pada UMKM Lingkungan Pasar Yaahowu - Helentina Zebua; Emanuel Zebua; Yupiter Mendrofa; Idarni Harefa (LPPM Universitas HKBP Nommensen, 2024)
This study examines the digital promotion strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) in Yaahowu Market, Gunungsitoli City, and their impact on increasing sales volume. In the increasingly advanced digital era, the adoption of digital technology is important for MSMEs to increase the competitiveness and visibility of their products. This study found that education and training on the use of digital platforms such as social media and e-commerce are crucial for MSMEs who are new to digital technology. Social media has proven effective in attracting new customers, while online marketplaces such as Tokopedia, Bukalapak, and Shopee provide opportunities for MSMEs to expand their market reach. This conclusion highlights the importance of evaluating and adjusting strategies based on the data obtained to ensure the effectiveness of digital promotion campaigns, as well as the need for ongoing support for MSMEs in facing challenges in the digital era.